Poly[(N-acryloyl glycinamide)-co-(N-acryloyl l-alaninamide)] and Their Ability to Form Thermo-Responsive Hydrogels for Sustained Drug Delivery - Mahfoud Boustta; Michel Vert (Gels, 2019)
In the presence of water, poly(N-acryloyl glycinamide) homopolymers form highly swollen hydrogels that undergo fast and reversible gel↔sol transitions on heating. According to the literature, the transition temperature depends on concentration and average molecular weight, and in the case of copolymers, composition and hydrophilic/hydrophobic character. In this article, we wish to introduce new copolymers made by free radical polymerization of mixtures of N-acryloyl glycinamide and of its analog optically active N-acryloyl l-alaninamide in various proportions. The N-acryloyl l-alaninamide monomer was selected in attempts to introduce hydrophobicity and chirality in addition to thermo-responsiveness of the Upper Critical Solubilization Temperature-type. The characterization of the resulting copolymers included solubility in solvents, dynamic viscosity in solution, Fourrier Transform Infrared, Nuclear Magnetic Resonance, and Circular Dichroism spectra. Gel→sol transition temperatures were determined in phosphate buffer (pH = 7.4, isotonic to 320 mOsm/dm3). The release characteristics of hydrophilic Methylene Blue and hydrophobic Risperidone entrapped in poly(N-acryloyl glycinamide) and in two copolymers containing 50 and 75% of alanine-based units, respectively, were compared. It was found that increasing the content in N-acryloyl-alaninamide-based units increased the gel→sol transition temperature, decreased the gel consistency, and increased the release rate of Risperidone, but not that of Methylene Blue, with respect to homo poly(N-acryloyl glycinamide). The increase observed in the case of Risperidone appeared to be related to the hydrophobicity generated by alanine residues.